ANALISIS KETIMPANGAN PENYERAPAN TENAGA KERJA SEKTOR INDUSTRI PENGOLAHAN DI KABUPATEN/KOTA JAWA TIMUR - Aprilia, Wahyuni; Sudarti, .; Hadi, Syamsul (Jurnal Ekonomi Pembangunan, 2016)
This study aims to analyze existence of inequality of employment absorption and determine the effect of the minimum salary, the number of manufacturing industry, and output of manufacturing industry towards inequality of employment absorption of manufacturing industry in regencies/cities of East Java in 2008-2012. The data collection method uses documentation method. Then, The writer uses the Index Entropy Theil (IET) to measure inequality of employment absorption as dependent variable. Meanwhile, to determine the effect of independent variable toward the dependent variable uses method regression analysis panel data with model common effect approach. The results of this study shows that there are inequality of employment absorption of manufacturing industry in East Java province of the Year 2008-2012. Minimum salary, the number of manufacturing industry, and theoutput of manufacturing industry effect positive and significant effect on inequalityof employment absorption ofmanufacturing industry in regions/cities in East Java.